Pengaruh Promotion, Visual Merchandising dan Personal Selling terhadap Minat Beli Konsumen PT Shafco Multi Trading Medan - Al Firah; Nella Ulfa Siregar (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of promotion, visual merchandising, and personal selling in increasing consumer buying interest and using a quantitative method with a sample of 50 people tested through multiple linear regression. The results of the partial study (t test) show that there is a significant influence between Promotion on Purchase Interest, tcount ≥ t table, namely 4.158 > 1.67722) so that Ha is accepted (Ho is rejected). There is a significant influence between Visual Merchandising on Purchase Intention (t count ≥ t table, namely 2.425 > 1.6772) so that Ha is accepted (Ho is rejected). There is a significant influence between Personal Selling on Purchase Intention (t count ≥ t table, namely 3.502 > 1.67722) so that Ha is accepted (Ho is rejected). The results of the study simultaneously (F test), there is a significant influence between Promotion, Visual Merchandising, and Personal Selling on Buying Interest at PT. Shafco Multi Trading Medan (Fcount ≥ Ftable, namely 47.950 > 3.20) with a significance of 0.000 <0.05 while the Ftable value is based on N with a significant level of 5%, namely dk = n – k– 1 then 50 - 2 - 1 = 47 is 3,20. Because Fcount < Ftable then Ha is accepted (Ho is rejected). The results of the Determination test show that the influence of Promotion, Visual Merchandising, and Personal Selling on Consumer Purchase Interest is 0.758 or 75.8%, while the remaining 24.2% is influenced by other factors not included in this study.